Impact of Obesity on Clinicopathologic Characteristics and Disease Prognosis in Pre- and Postmenopausal Breast Cancer Patients: A Retrospective Institutional Study - Nehad M. Ayoub; Rami J. Yaghan; Nour M. Abdo; Ismail I. Matalka; Laila M. Akhu-Zaheya; Alia H. Al-Mohtaseb (Journal of Obesity)
Purpose. To investigate the association between obesity and breast cancer clinicopathologic characteristics at presentation along with prognostic impact among Jordanian breast cancer patients. Such data are lacking in Arabian countries. Methods. In this retrospective study, 348 breast cancer patients were included. Analyses were conducted for associations between body mass index (BMI) and age at diagnosis, tumor clinicopathologic characteristics, and molecular subtypes. Eight prognostic factors were considered, and total prognostic scores were calculated. The analysis was stratified by menopausal status. Multivariate logistic stepwise regression analysis was conducted to identify predictors for breast cancer recurrence and death. Results. Mean age at diagnosis was 50.98 ± 10.96 years. Mean BMI at diagnosis was 29.52 ± 5.32 kg/m2. Mean age at diagnosis was significantly higher for overweight and obese patients compared to underweight/normal patients (P<0.001). A significant positive correlation was observed between patient age and BMI at diagnosis (r = 0.251, P<0.001). Grade of carcinoma was significantly correlated with BMI in the whole population examined (P=0.003). Obese breast cancer patients had significantly higher prognostic scores compared to nonobese cases, indicating worse prognostic features at presentation (P=0.034). Stratification of data analysis based on menopausal status revealed significant associations between obesity and each of tumor stage and grade among postmenopausal but not premenopausal patients (P=0.019 and P=0.031, respectively). Similarly, postmenopausal obese patients had significantly higher prognostic scores compared to nonobese counterparts (P=0.007), indicating worse prognosis, a finding which was also absent among premenopausal breast cancer patients. No significant association between BMI with expression status of hormone receptors, HER2, lymphovascular invasion, and molecular subtypes was found among patients. BMI was a significant predictor for disease recurrence in which obese breast cancer patients had greater odds (2-fold) to develop locoregional and distant recurrence compared to nonobese cases (P=0.011). Conclusions. Obesity was associated with advanced stage and grade of breast carcinoma at diagnosis. The impact of BMI on clinicopathologic characteristics and prognosis was confined to postmenopausal cases. Jordanian obese breast cancer patients are at greater risk of breast cancer recurrence and reduced survival compared to their nonobese counterparts.